ARIC Hemostasis Study - III. Ouality Control - Chambless, Lloyd E; McMahon, Robert; Finch, Andrea; Sorlie, Paul; Heiss, Gerardo; Lyles, Robert; Wu, Kenneth K (Thrombosis and Haemostasis, 1993)
Methods and results from the quality assurance program of the Atherosclerosis Risk in Communities (ARIC) Study regarding hemostasis variables are presented, following up previous reports in this journal on standardized procedures for blood collection and processing (7) and an organized plan for the performance of those procedures (8). Efforts were made to control for and assess all sources of variability, from venipuncture to laboratory analysis, including also local field center processing and sample shipping. The quality control program included (a) a standardized protocol for blood collection and processing; (b) training, certification, and annual recertification of field center personnel for blood collection and processing; (c) monitoring of fasting times, phlebotomy times, processing times, and shipping problems; (d) hemostatic laboratory internal quality control; (e) a replicate blood sample program; (f) an intraindividual variability study; and (g) continual monitoring of quality control and study participants’ data. This paper focused on items (c), (d), and (e). Measures of Variation, generally Standard deviations and coefficients of Variation, are estimated for replicate blood sampling and internal quality control data, for activated partial thromboplastin time, fibrinogen, factor VII and VIII activity, von Willebrand factor, antithrombin-III, and protein C. The results demonstrate that it is possible to reliably measure these hemostatic variables in a large multicenter study.